THE INFLUENCE OF PROFITABILITY, LIQUIDITY, SOLVENCY, COMPANY SIZE ON AUDIT REPORT LAG IN BASIC INDUSTRY AND CHEMICAL COMPANIES LISTED ON BEI FOR THE 2019-2021 PERIOD - maggie; Mutiara Wijaya; Yois Nelsari Malau; Wenny Anggeresia Ginting (Journal Accounting International Mount Hope, 2024)
The Indonesian Stock Exchange (BEI) or Indonesia Stock Exchange (IDX) is a party that organizes and provides systems and facilities to bring together offers to buy and sell securities from other parties. In the IDX there are several company sectors where in this research the basic industrial and chemical company sectors were selected. The company's timeliness in publishing financial reports depends on the auditor's timeliness in completing the report. Timeliness in reporting finances is related to several variables that will be studied so this research aims to determine the influence of profitability, liquidity, solvency and company size on audit report lag in basic industrial and chemical companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The number of samples used was 76 companies using quantitative analysis methods. The research technique used was the purposive sampling method. The research results show that (1) profitability has a negative effect on audit report lag, indicating that a high level of profitability can complete the audit process in a shorter time. (2) liquidity has no effect on audit report lag, indicating that a high level of liquidity can delay the publication of financial reports. (3) solvency has a positive effect on audit report lag, it can be indicated that a high level of solvency reflects the company's financial risk, high company financial risk indicates the company is experiencing financial difficulties. (4) company size has a positive effect on audit report lag, indicating that a larger company means it has a good control system so that it can reduce errors in submitting financial reports.